2018
DOI: 10.1080/00221546.2018.1442983
|View full text |Cite
|
Sign up to set email alerts
|

No Time for College? An Investigation of Time Poverty and Parenthood

Abstract: Postsecondary outcomes are significantly worse for student parents even though they earn higher G.P.A.'s on average. This study used institutional records and survey data from a large urban U.S. university to explore whether time poverty explains this trend. The results of regression and KHB decomposition analysis reveal that students with preschool-aged children have a significantly lower quantity and quality of time for college than comparable peers with older or no children, and that time spent on childcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 21 publications
5
50
0
Order By: Relevance
“…The majority of these student–parents are women (Institute for Women’s Policy Research and Ascend at the Aspen Institute, 2019) and over two fifths of student–parents are single mothers (Cruse, Holtzman, Gault, Croom, & Polk, 2019). Although student–parents earn higher grades and have higher GPAs than their nonparent peers (Institute for Women’s Policy Research and Ascend at the Aspen Institute, 2019), over half of student–parents (52%) drop out within six years of enrolling in school (Wladis, Hachey, & Conway, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The majority of these student–parents are women (Institute for Women’s Policy Research and Ascend at the Aspen Institute, 2019) and over two fifths of student–parents are single mothers (Cruse, Holtzman, Gault, Croom, & Polk, 2019). Although student–parents earn higher grades and have higher GPAs than their nonparent peers (Institute for Women’s Policy Research and Ascend at the Aspen Institute, 2019), over half of student–parents (52%) drop out within six years of enrolling in school (Wladis, Hachey, & Conway, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Undoubtedly, these multiple roles create a strain on a student–parent and can place them at greater risk of dropping out of school compared to the traditional college student. It was found that student–parents with preschool children demonstrated that the demands of balancing their time between their studies, work, and caring for their dependent child had resulted in not only a delay in degree completion but dropping out completely from their studies (Wladis et al, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The financial insecurity, difficulty in meeting basic needs of life, and substantial caregiving demands negatively impact student-parents' chances for degree completion and significantly strain their physical and mental health. 9,10 Clearly, this parent-population in higher education overlaps with other vulnerable populations that most institutions focus on-minority, low-income, and first-generation students. 11 The vulnerabilities of the student-parent population, however, may well exceed those of other populations because of the additional challenges of family care duties.…”
Section: Introductionmentioning
confidence: 99%